2006
DOI: 10.1086/507431
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 33 Polymorphisms and High‐Grade Squamous Intraepithelial Lesions of the Uterine Cervix

Abstract: Intratypic LCR variants of HPV-33 seem to vary geographically and to differ with respect to their oncogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 43 publications
8
42
1
1
Order By: Relevance
“…HPV16 and -33 are high-risk HPVs frequently detected in cervical cancer. Naturally occurring variants of HPV16 and -33 with polymorphisms in the E6 open reading frame (ORF) have been reported (18,22,32,58,72), some of which have been linked to oncogenicity (23,47,73). To investigate whether these polymorphisms have an impact on p53 degradation by E6, we performed p53 expression assays in the presence of HPV16 E6 variants R10G, L83V, and R10G/L83V, as well as HPV33 E6 K35N (N), K35N/N86H (NH), I73L/V83L/K93N/ A138V (LLNV), P36T/I73L/V83L/K93N/A138V (TLLNV), and A18V/P36T/I73L/V83L/K93N/A138V (VTLLNV) and the prototype HPV16 E6 and HPV33 E6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HPV16 and -33 are high-risk HPVs frequently detected in cervical cancer. Naturally occurring variants of HPV16 and -33 with polymorphisms in the E6 open reading frame (ORF) have been reported (18,22,32,58,72), some of which have been linked to oncogenicity (23,47,73). To investigate whether these polymorphisms have an impact on p53 degradation by E6, we performed p53 expression assays in the presence of HPV16 E6 variants R10G, L83V, and R10G/L83V, as well as HPV33 E6 K35N (N), K35N/N86H (NH), I73L/V83L/K93N/ A138V (LLNV), P36T/I73L/V83L/K93N/A138V (TLLNV), and A18V/P36T/I73L/V83L/K93N/A138V (VTLLNV) and the prototype HPV16 E6 and HPV33 E6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An even higher disconcordance rate was detected by pyrosequencing of HPV-16 variants in a recent study of human immunodeficiency virus-infected adults [14]. Other studies have reported identical variants in consecutive samples positive for HPV-16 [11,12] or other high-risk types [15]. Although the inconsistent results can in part be explained by differences in study populations, interval durations, and approaches for variant characterization, most of these studies were limited by small sample size.…”
Section: Prospective Studies Of the Persistence Of Human Papillomavirmentioning
confidence: 98%
“…The non-E HPV 18 variants are more frequently identified in cancer tissues and high-grade lesions (23)(24)(25) . HPV 33 (C7732G) and HPV 58 (C632T and G760A) variants were associated with a higher risk for cervical cancer (26,27) than that observed for infectios with "prototypes" of the same HPV 33 and 58.…”
Section: Introductionmentioning
confidence: 85%